2020
DOI: 10.3389/fneur.2020.00705
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Visual Deficits Independent of Lesion Site in Acute Stroke

Abstract: Most clinical diagnoses of stroke are based on the persistence of symptoms relating to consciousness, language, visual-field loss, extraocular movement, neglect (visual), motor strength, and sensory loss following acute cerebral infarction. Yet despite the fact that most motor actions and cognition are driven by vision, functional vision per se is seldom tested rigorously during hospitalization. Hence we set out to determine the effects of acute stroke on functional vision, using an iPad application (Melbourne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…Currently, there are little reliable data about how well individuals with severe respiratory system and lung damage will recover or whether scarring will make such patients vulnerable to other viral infections ( 31 ). Furthermore, questions remain regarding whether the hypoxia engendered during the acute hospitalization phase will have lasting effects on the brain and nerve tissue especially on high metabolic demand areas including the sympathetic system and the fast visual attention and eye movements pathways ( 112 ) and long motor pathways.…”
Section: Covid Neurological Manifestations and Implications For Neurmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, there are little reliable data about how well individuals with severe respiratory system and lung damage will recover or whether scarring will make such patients vulnerable to other viral infections ( 31 ). Furthermore, questions remain regarding whether the hypoxia engendered during the acute hospitalization phase will have lasting effects on the brain and nerve tissue especially on high metabolic demand areas including the sympathetic system and the fast visual attention and eye movements pathways ( 112 ) and long motor pathways.…”
Section: Covid Neurological Manifestations and Implications For Neurmentioning
confidence: 99%
“…For further details, see Mantovani et al and the 29 recommendations on evidence-based cognitive rehabilitation in the context of stroke and TBI nominated by the Cognitive Rehabilitation Task Force (CRTF), which suggests that a more comprehensive biological understanding of the various systems affected by TBI should lead to more collaborative translational research utilizing artificial intelligence and novel technology to find better individually designed precision solutions (e.g., video-consults, tablet-based measurements, and use of wearable devices). Lastly, the integration of services, including private and public partnerships such as university–public hospital partnerships and partnerships with community organizations and volunteers, are likely to create excellent opportunities for the future ( 112 , 154 , 155 ) and better evidence-based neurorehabilitation pathways.…”
Section: Covid Neurological Manifestations and Implications For Neurmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, these circumstances argue a strong case for converting the catastrophe [Complex rearrangement of hospital facilities as part of the preparation for the pandemic has also occasioned significant problems and added resource problems for health care systems across the world (44)(45)(46)(47)(48)(49)(50) into an opportunity for revamping of rehabilitation protocols]. Currently evidence is emerging for further expansion of telemedicine type paradigms, with incorporation of tablet based remote monitoring technology (Melbourne Rapid Field visual fields, wearable devices and artificial intelligence) suggesting as the way forward in neurorehabilitation of AIS in COVID19 pandemic era, at least for the foreseeable future (43,(51)(52)(53).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials have reported that ∼70% of referred stroke survivors posthospitalization have ipsilaterally derived eye movement disorders (12)(13)(14)(15) and reduced amplitude in micro-saccades which may affect visual sensitivity (16). We have also recently reported that ∼2/3 of mild-moderate severity first episode acute ischemic stroke (AIS) patients with no previous history of impaired vision, experience deteriorated visual acuity-in-noise (VAn) with contralateral visual field defects immediately (i.e., within 7 days) after stroke (17). Given the ubiquity of motor involvement in stroke, we set out to examine and quantify visuomotor performance in the same group of hospitalized AIS cases whose sensory visual capacity was reported in the past (17), and for this study, we added a motor eye-hand coordination task.…”
Section: Introductionmentioning
confidence: 99%